2020
DOI: 10.3390/ijerph17239001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extreme Temperatures on Ambulance Dispatches Due to Cardiovascular Causes in North-West Spain

Abstract: Introduction and objectives. The increase in mortality and hospital admissions associated with high and low temperatures is well established. However, less is known about the influence of extreme ambient temperature conditions on cardiovascular ambulance dispatches. This study seeks to evaluate the effects of minimum and maximum daily temperatures on cardiovascular morbidity in the cities of Vigo and A Coruña in North-West Spain, using emergency medical calls during the period 2005–2017. Methods. For the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Onozuka and Hagihara (2015) 43 reported that 18.02% of emergency call-outs were attributable to non-optimal temperatures, with the majority of these (17.93%) being due to low non-optimal temperatures. Of this fraction, 16.92% were attributed to moderately low temperatures (between the 96th and 2.5th centiles), with only 19 in two cities in the northwest of Spain, with a significant effect of low temperatures observed in only one city (A Corunã).…”
Section: Effects Of Low Temperatures On Ambulance Call-outs For Cardi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Onozuka and Hagihara (2015) 43 reported that 18.02% of emergency call-outs were attributable to non-optimal temperatures, with the majority of these (17.93%) being due to low non-optimal temperatures. Of this fraction, 16.92% were attributed to moderately low temperatures (between the 96th and 2.5th centiles), with only 19 in two cities in the northwest of Spain, with a significant effect of low temperatures observed in only one city (A Corunã).…”
Section: Effects Of Low Temperatures On Ambulance Call-outs For Cardi...mentioning
confidence: 99%
“…The effect was assessed in seven studies. 16,18,19,21,22,43,45 Although none assessed it during cold waves, they did assess it at extremely low centiles. The effects due to low temperatures were studied over the course of the year in four studies 16,19,21,43 and during the cold season in three.…”
Section: Effects Of Low Temperatures On Ambulance Call-outs For Cardi...mentioning
confidence: 99%
See 3 more Smart Citations